The Influence of Application Based Information Technology Usage on the Loyalty and Retention of Gojek Partner Drivers in Jabodetabek - Widanengsih, Euis; Agustini, Fajar; Suwanto, Suwanto (Jurnal Multidisiplin Sahombu, 2025)
This study examines the influence of application-based information technology usage on the loyalty and retention of Gojek partner drivers in Jabodetabek. Employing a quantitative explanatory approach, data were collected through a five-point Likert scale questionnaire from 100 active drivers selected via purposive sampling. The constructs measured include ease of use, system reliability, information quality, and user interaction as independent variables, with loyalty and retention as dependent variables. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to assess measurement validity, reliability, and structural relationships. The results show that application-based information technology usage significantly and positively affects both loyalty and retention. However, loyalty does not significantly influence retention, and mediation analysis indicates that loyalty does not mediate the relationship between technology usage and retention. These findings suggest that technology’s impact on retention is primarily direct, highlighting the need for continuous improvements in usability, reliability, and transparency to sustain driver engagement in a competitive ride-hailing market.